Synthesizing Pedagogies and Engaging Students: Creating Blended eLearning Strategies for Library Research and Writing Instruction. Issue 4 (1st October 2016) - Kitchens, Rhonda K.; Barker, Mary Ellen
ABSTRACT: Twenty-first century students need consideration, ideas, and face-to-face work to enable their success in acquiring new information. Twenty-first century skills are generally described as core competencies such as collaboration, digital literacy, critical thinking, and problem solving. Collaborative work between the classroom instructor and the librarian builds digital reference and research materials to follow a scaffolded research project specifically from start to finish. This article identifies reference opportunities and the importance of online and face-to-face student support. Instead of a linear approach to information literacy, this article demonstrates a chunked eLearning in-context performance support style.